Response of nitrogen fertilization on Bt and non-Bt cotton (Gossypium hirsutum) hybrids - Gangaiah, B; Ahlawat, IPS; Babu, MBBP (SAARC Journal of Agriculture, 2014)
A field experiment was conducted during 2006 and 2007 (June- December) at New Delhi to assess the performance of three cotton hybrids of which two Bt (MRC 6304 & RCH 317) and one non-Bt cotton hybrid LHH 144 (North zone check) in response to nitrogen fertilization (0, 60, 120 and 180 kg ha-1). Based on pooled analysis, both Bt hybrids produced similar seed cotton yield (SCY). Bt hybrid have produced 7.1 bolls/plant (on an average) and bolls 0.48 g heavier than non Bt hybrid LHH 144 that lead to 1.07 t ha-1 higher SCY of Bt hybrids than non-Bt hybrid (1.93 t ha-1). Though the N uptake by cotton hybrids was statistically similar N harvest index (NHI) was higher in Bt hybrid (57.85) as compared to non-Bt hybrid (40.5). The agronomic N use efficiency (ANUE) was highest in MRC 6304 Bt (6.44) and least in LHH 144 non-Bt cotton (3.91). Cotton growth, yield attributes, SCY, and N uptake increased with each successive increase to the highest level of 180 kg ha-1 however, the N response of cotton was quadratic in nature with optimum dose of 173.0 kg ha-1. The NHI decreased with increase in N dose i.e. from the highest of 56.3 in control to the lowest of 48.8 with 180 kg ha-1 N fertilization. ANUE and physiological NUE that was highest with 60 (5.73) and 120 kg N fertilization (17.05), respectively and decreased with further increase in N dose. The cotton hybrid x N interaction effect revealed that Bt cottons have quadratic N response while non-Bt cotton has linear N response. From the economic point of view, Bt hybrids with 120 kg Nha-1 could be optimum dose for cotton cultivation. DOI: http://dx.doi.org/10.3329/sja.v11i1.18389 SAARC J. Agri., 11(1): 121-132 (2013)